Small interfering RNA delivery through positively charged polymer nanoparticles. (18th February 2016) - Dragoni, Luca; Ferrari, Raffaele; Lupi, Monica; Cesana, Alberto; Falcetta, Francesca; Ubezio, Paolo; D'Incalci, Maurizio; Morbidelli, Massimo; Moscatelli, Davide
Abstract: Small interfering RNA (siRNA) is receiving increasing attention with regard to the treatment of many genetic diseases, both acquired and hereditary, such as cancer and diabetes. Being a high molecular weight (MW) polyanion, siRNA is not able to cross a cell membrane, and in addition it is unstable in physiological conditions. Accordingly, a biocompatible nanocarrier able to deliver siRNA into cells is needed. In this work, we synthesized biocompatible positively charged nanoparticles (NPs) following a two-step process that involves ring opening polymerization (ROP) and emulsion free radical polymerization (EFRP). Firstly, we proved the possibility of fine tuning the NPs' characteristics (e.g. size and surface charge) by changing the synthetic process parameters. Then the capability in loading and delivering undamaged siRNA into a cancer cell cytoplasm has been shown. This latter process occurs through the biodegradation of the polymer constituting the NPs, whose kinetics can be tuned by adjusting the polymer's MW. Finally, the ability of NPs to carry siRNA inside the cells in order to inhibit their target gene has been demonstrated using green flourescent protein positive cells.